TERAPI ZIKIR DALAM MENURUNKAN STRES ( STUDI KASUS REMAJA MASJID JAMI' NURUL AMIN TONYAMAN KABUPATEN POLEWALI MANDAR) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This study aims to determine the form of remembrance therapy in reducing stress for adolescents at Jami' Nurul Amin Mosque Tonyaman, Polewali Mandar Regency. The impact of remembrance therapy in reducing stress for adolescents at Jami' Nurul Amin Mosque Tonyaman, Polewali Mandar Regency. This study uses a descriptive qualitative research type located at Jami' Nurul Amin Mosque, Tonyaman Village, Polewali Mandar Regency. The research approach used is the Islamic Counseling Guidance approach and the Psychology approach. Data collection methods are observation, interviews, and documentation. The data processing and analysis technique was carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that, the form of remembrance therapy in reducing stress for adolescents at Jami' Nurul Amin Tonyaman Mosque, Polewali Mandar Regency, namely in the form of remembrance Qauly remembrance which is spoken orally by uttering praises of praise to Allah and can be heard by the ear, remembrance of Qalby remembrance which is done by remembering Allah with the heart, in other words remembering Allah with the heart, and dhikr fi'ly or remembering Allah in the form of action in question is every act or activity of a person who is good and can lead him to remember Allah or as an action based on God's rules and regulations. The impact of remembrance therapy in reducing stress for teenagers at Jami' Nurul Amin Mosque Tonyaman, Polewali Mandar Regency, namely making the heart peaceful, increasing confidence and courage, eliminating fear, and softening the heart.The implications of this research are: The mosque youth program, whether the mosque's imam or mosque youth coach, makes a series of lessons in special material about remembrance about its meaning, purpose, and benefits. The remembrance activities should be scheduled for several different mosques so that the remembrance is not only followed by teenagers with the same hamlet or only one hamlet.